QCGN Statement on Murder of Muslim Family in London, Ontario : Human Rights and Freedoms Are Not to be Taken for Granted - Quebec Community Groups Network (QCGN) (2021)

The Positive Ticket Pilot Program : A Feasibility Study - Low, Katherine (Black Community Resource Centre (BCRC), 2009)
The Positive Ticket Project was started in Richmond BC, and aims to improve the relationship between youth and police by way of positive interaction. Officers give out the positive tickets to neighbourhood youth displaying positive behaviour, which can be as simple as engaging in safe play or helping a community member. The positive tickets, which are business card size with positive messages printed on them, are combined with gift vouchers donated by and redeemable at local businesses. The real value of the project lies in the positive communication and interaction it creates between the officer and the youth. The Black Community Resource Center in Côte-des-Neiges wishes to implement a Positive Ticket Pilot Project in their neighbourhood in the summer of 2010.

Press Conference - Alliance Quebec (AQ) (2002)